The International Comparison of Strategies for Reading Comprehension from Teacher Preference: A Review of Selected Paper - Silalahi, Novia Sariahta (English Education:Journal of English Teaching and Research, 2019)
This paper intended to explore and giving an overview in strengths and weakness part of the proposed strategies in reading comprehension. The 18 pages article written by Scott Kissau and Florian Hiller (2013), entitled "Reading Comprehension Strategies: an international comparison of teacher preferences" the which is published in RCIE, volume 8, number 4, 2013. This article is the main focuses of this present study to discuss. The article was selected as this article focus to discuss an act in response to the panic world will lack the ability of reading comprehension at the moment of the millennial era. This research was conducted at a university located in the United States and Germany with participant prospective teachers in different contexts. By using a quantitative and qualitative data researcher general preference among participants from both countries studied to better understand what is considered an effective strategy in a particular content area and investigate the reading comprehension strategies that favoured prospective teachers in Germany and the United States in a variety of different contexts. And expecting their further studies involving participants from a large number of universities of different countries so as to produce variations in the results and generate the appropriate strategy to use in reading certain content. This paper using content analysis method. By using a quantitative and qualitative data researcher general preference among participants from both countries studied to better understand what is considered an effective strategy in a particular content area and investigate the reading comprehension strategies that favoured prospective teachers in Germany and the United States in a variety of different contexts. This presents study sees that the result from Scott Kissau and Florian Hiller research can be replicable. Therefore it is expecting another further study involving participants from a large number of universities of different countries so as to produce variations in the results and generate the appropriate strategy to use in reading certain content.